Building Customer Loyalty Through Experiential marketing - Ardini, Sarah Fadhila; Lubis, Nurul Wardani; Tarigan, Nimia Eliani Br; Siburian , Kristina Mesya Yulianti; Sitindaon, Natanael (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This study aims to describe and analyze the influence of Experiential marketing on customer loyalty. The main focus is how experiential marketing can create strong loyalty through meaningful and relevant experiences for consumers. The method used in this study is the literature review approach. Data collection was carried out by referring to existing studies, such as scientific articles, journals, books, and research reports published in the last five years. This analysis focuses on how Experiential marketing affects customer loyalty based on various relevant literature sources. The results of the study show that Experiential marketing is able to create strong customer loyalty by presenting meaningful experiences for consumers. This approach has proven to be more effective than traditional marketing that only focuses on price or product quality. Experiential marketing not only provides information, but also triggers consumer emotions and feelings, which leads to increased sales. Experiential marketing is a core element in creating value for customers. By focusing on relevant and emotionally engaging experiences, companies can build strong and sustainable loyalty. It also helps create competitive advantage and sustainable growth to support the business as a whole.